1992
DOI: 10.1002/1098-2337(1992)18:5<349::aid-ab2480180504>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Aggression-consistent, -inconsistent, and -irrelevant priming effects on selective exposure to media violence

Abstract: Priming with aggressive concepts increases males' attraction to media violence. It was hypothesized that priming with schema‐irrelevant concepts would decrease interest relative to the effects of schema‐relevant concepts, whether or not the schema‐relevant concepts were also schema‐consistent. Thirty male undergraduates used lists including aggressive (schema‐consistent and schema‐relevant), positive or prosocial (schema‐inconsistent yet relevant), or entirely neutral (schema‐irrelevant) words to write short s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Several alternative gratifications for viewing violence have been proposed [see Goldstein, ; Sparks and Sparks, ]. For example, watching violent content could help viewers reinforce their belief in a just world or could provide some sense of control in times of stress [e.g., Boyanowsky et al, ; Langley et al, ], neither of which would necessarily increase “enjoyment” as it is conceptualized here. Media violence could also help viewers fulfill expectations associated with social norms [e.g., Zillmann et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Several alternative gratifications for viewing violence have been proposed [see Goldstein, ; Sparks and Sparks, ]. For example, watching violent content could help viewers reinforce their belief in a just world or could provide some sense of control in times of stress [e.g., Boyanowsky et al, ; Langley et al, ], neither of which would necessarily increase “enjoyment” as it is conceptualized here. Media violence could also help viewers fulfill expectations associated with social norms [e.g., Zillmann et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Trait aggression has been found to moderate the effect of media violence on aggression, such that individuals high in trait aggression are more susceptible to this effect (Bushman, 1995). Many studies also have found that aggressive individuals are drawn to violent programming (e.g., Fenigstein, 1979; Langley, O'Neal, Craig, & Yost, 1992). That is, individuals who are highly aggressive are more likely to select violent programs than nonviolent programs when given a choice, and individuals who score low in aggression are more likely to choose nonviolent programs.…”
Section: The Role Of Individual Differences In Enjoymentmentioning
confidence: 99%
“…Studies showing the role of automatic processes typically assume an automatic and direct perception-behavior path as postulated in the auto-motive model (Bargh, 1990). That model argues that if anyone primed by an aggressive concept via subliminal priming or via a provocation automatically acts aggressively because the concept is temporarily accessible and triggers relevant cognitive activities that lead to behavior without need for conscious or deliberative decision making (Langley, O’Neal, Craig, & Yost, 1992; for a review on automatic sources of aggression, see Todorov & Bargh, 2001). However, Perugini and Prestwich (2007) suggested that the auto-motive model fails to consider the role of individual differences in the perception-behavior path.…”
Section: Introductionmentioning
confidence: 99%